2021
DOI: 10.3390/jcm10051088
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Sexual Dysfunction in Men

Abstract: Sexual issues tend to go unaddressed in human immunodeficiency virus (HIV) management, although overt sexual dysfunctions are more prevalent in people living with HIV than uninfected people. Erectile dysfunction is the most frequent sexual problem, with a prevalence of 30–50% even in men <40 years of age, but other issues such as loss of libido and ejaculatory disorders should not be overlooked. Peculiar factors related to HIV infection (e.g., fear of virus transmission, changes in body image, HIV-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 195 publications
(346 reference statements)
6
43
0
Order By: Relevance
“…There has been a neglected aspect of reproductive dysfunction in human immunodeficiency virus 1 (HIV-1) infected persons, with increasing reports of reproductive dysfunctions (RDs) in these people under antiretroviral drugs 1 . Although RDs are part of HIV complications widely reported in the literature before introducing highly active antiretroviral therapy (HAART) 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been a neglected aspect of reproductive dysfunction in human immunodeficiency virus 1 (HIV-1) infected persons, with increasing reports of reproductive dysfunctions (RDs) in these people under antiretroviral drugs 1 . Although RDs are part of HIV complications widely reported in the literature before introducing highly active antiretroviral therapy (HAART) 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sexual disorders, especially ED, in men with other STIs such as human immunodeficiency virus (HIV) and Herpes simplex virus (HSV) has also been reported, like HPV [ 8 , 10 ]. In these diseases, in addition to atherosclerotic changes and problems with the organic vascular component sexual function that occurs in some diseases such as HSV, seems to cause psychological distress and emotional concerns about the possibility of partner involvement and the appearance of skin lesions, which can lead to the high attention to sexual performance during intercourse and lead to ED [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been shown that STIs have negative effects on men’s mental health and sexual function [ 8 10 ]. Some studies also indicate sexual-related concern in men with GWs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,25 A slight decrease in sexual frequency has been observed in some couples after finding out their HIV-1 positive status (68.42% per week before infection to 57.90% after infection). Indeed, a study conducted by De Vincentis et al 26 has shown that some HIV-1 seropositive men are more at risk of having difficulty obtaining and maintaining an erection, and may experience a decrease in their sexual desire and their libido.…”
Section: Discussionmentioning
confidence: 99%